Gestão de projetos colaborativos entre organizações: Um estudo da relação Unisinos e Hospital Mãe de Deus - Bohn, Patricia Raquel (Universidade do Vale do Rio dos Sinos, 2012)
The cooperation among the organizations has emerged in response to the requests of the competitive and unstable environment of the last decades. It has shown as a viable alternative to the survival and expansion of the companies. The development of collaborative projects follows such tendency as the complex activities are developed among the organizations in a shared way and for a determined period of time, aiming to unite capacities and competencies to reach specific results. The expansion of the collective strategies under a collaborative projects format has created some questioning regarding the sort of management to be employed. Although there are studies that contemplate the sort of management in the cooperative relationships among the organizations their analysis is still incipient in a context of project. Therefore, the presented essay treats the subject collaborative projects management among the organizations. The general objective consists on identifying and analyzing the characteristics of the collaborative projects management among the organizations aiming to answer how it occurs. Thus, the theorical review focused on topics regarded the cooperation among the organizations, the cooperation background and results, sort of management as well as the aspects related to the collaborative projects. As an investigative strategy the qualitative research was chosen through a unique case study with incorporated units. The data was acquired through fourteen in-depth interviews and secondary data. After the collection, it was introduced the analysis of the qualitative content. As the research’s result, it was concluded the main project’s antecedents are linked to the actors’ similarity, interdependence, efficiency and legitimacy. Among the main benefits there are the gain of scale, learning, knowledge and innovation. As a crucial topic of the research, it was noticed the way of the power relationship establishment and the formality among the agents, as well as the used mechanisms of coordination that were dependent of the particularities and specifities of each project influencing the collaborative projects management among the organizations. Furthermore, the empiric evidences tend to demonstrate as the greater project’s complexity and its strategic importance to the institutions the more specific and formal tend to be the used mechanisms of coordination to its management.
Keywords: Management; Collaborative projects; Cooperation; Gestão; Projetos colaborativos; Cooperação; ACCNPQ::Ciências Sociais Aplicadas::Administração